Willingness to Get Vaccinated and Attitude Toward COVID-19 among Humanities and Social Sciences Students - Athena Ella G. Antepuesto; Dennis A. Coja, Jr.; Therese Carmel C. Comeros; Juliana Mae T. Flores; Flordeliza S. Gagani; Vea Marielle T. Guantero; Daven Egan D. Labitad; Anne Valerie S. Torrejos (Newinera Publisher, 2022)
Divergent viewpoints about COVID-19 health guidelines continue to impact the collective effort to reduce COVID-19 transmission. Thus, this descriptive-correlational study was conducted to determine if there is a significant relationship between the level of willingness to get vaccinated against COVID-19 and the attitude toward COVID-19 among sixty randomly selected Grade 12 Humanities and Social Sciences students of the University of San Carlos - South Campus in Cebu City, Philippines. Online data collection was done through two adapted and reliable Likert-type survey questionnaires. The findings indicated that the degree of willingness to be vaccinated was high (x = 3.79, SD = .98), while the level of attitude toward COVID-19 was very high (x = 4.36, SD = .75). Moreover, the correlation between the two variables was found to be significant, r(58) = 0.48, p = .000104, p < .05 at = .05. Therefore, the null hypothesis of no significant relationship was rejected, and the researchers found that there is a weakly positive correlation (r =.48) between the levels of willingness to be vaccinated and the students' attitude regarding COVID-19. This result indicates that their attitude toward COVID-19 improves in proportion to their vaccination willingness. This also suggests that adolescents who understand authorized COVID-19 vaccination guidelines are more eager to get the COVID-19 vaccine. The researchers recommend that more initiatives be developed to boost the public's desire and attitude toward COVID-19 immunization, and that additional research be conducted to validate results and examine trends in other communities.